Toxicological evaluation of mangiferin-loaded polymeric nanocapsules in Wistar rats - do Carmo, Guilherme; Dotto, Barbara; Borin, Diego Becker; Garcez, Renata; Vaucher, Rodrigo de Almeida; Baldissera, Matheus D.; Schwertz, Claiton I.; Mendes, Ricardo E.; Rech, Virginia Cielo; Raffin, Renata (Disciplinarum Scientia | Naturais e Tecnológicas, 2019)
This study aimed to verify the toxicological profile of nanocapsules containing mangiferin (NCM) in Wistar rats. Two administration routes, oral and intraperitoneal were evaluated. The animals were divided into 10 groups (n=8). The NCM were obtained with particle sizes of 69.1 ± 8.1 nm, polydispersity index of 0.12 ± 0.06 and zeta potential of -32.35 ± 4.03 mV. When administered orally, NCM and unloaded nanocapsules (UNC), as well as free mangiferin, did not alter any biochemical, hematological or histological parameter. The hematological analysis showed a significant increase (p<0.001) in total leukocytes in the groups UNC and NCM, and a significant decrease (p<0.01) in hemoglobin concentration and hematocrit in the group NCM through intraperitoneal administration. The biochemical analysis showed a significant increase (p<0.001) in the serum levels of urea and a significant decrease (p<0.001) in the serum levels of uric acid in the groups UNC and NCM administered intraperitoneally. The histological analysis showed an inflammatory process in the abdominal cavity of the groups UNC and NCM intraperitoneally. We observed that oral administration did not cause toxicity according to the evaluated parameters and was considered safe for use during a 24-day period. However, the intraperitoneal route was not appropriate for administering polymeric nanocapsules.